The simple truth - Baldacci, David (New York : Warner Books, 1998)
Twenty-five years after being convicted of the murder of a little girl, a black soldier discovers he was set up: someone drugged him to kill. When Rufus Harms appeals, the real killers come after him, so he breaks out of jail to help a lawyer bring them to justice.
Keywords: Political corruption -- United States -- Fiction; Detective and mystery fiction